Science Encyclopedia Based on the Compendium Al-Qur'an for Blind Students to Improve the Character of Science - Kartika, Ika (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2025)
This study aims to produce a science encyclopaedia based on summaries of the Qur'an for blind students. This type of research is Research and Development (R&D). The urgency of this research lies in the limited availability of accessible science learning resources with spiritual values for blind students, which poses a challenge in supporting inclusive and character-based education. The development was carried out with reference to a procedural model. The development procedure is based on 4-D. The results of this quality product development research show that the encyclopaedia, based on the assessment of science experts and media experts, has an excellent score, with an average score of 3.79 and 3.75. The quality of the developed product shows that the encyclopaedia based on the assessment of science teachers has a good score, with an average score of 3.06. The students' response in the small field test was very agreeable with an average score of 4. The research results conclude that the students' science character obtained through N-Gain analysis shows an average increase of 0.40, which is in the moderate criteria. The research findings indicate that the characters developed include curiosity, objectivity, responsibility, creativity, and critical thinking, as well as being able to increase the enthusiasm and learning experiences of visually impaired students in a more meaningful way. Thus, this product is effective in science learning to support inclusive character education based on Qur'anic values.